Novel 5-substituted 3-hydroxyphenyl and 3-nitrophenyl ethers of S-prolinol as α4β2-nicotinic acetylcholine receptor ligands. Issue 23 (1st December 2016) - Bolchi, Cristiano; Bavo, Francesco; Fumagalli, Laura; Gotti, Cecilia; Fasoli, Francesca; Moretti, Milena; Pallavicini, Marco
Graphical abstract: Abstract: A series of 3-nitrophenyl and 3-hydroxyphenyl ethers of ( S )- N -methylprolinol bearing bulky and lipophilic substituents at phenyl C5 were tested for affinity at α4β2 and α3β4 nAChRs. The two phenyl ethers 5-substituted with 6-hydroxy-1-hexynyl showed high α4β2 affinity and significantly increased α4β2/α3β4 selectivity compared to the respective unsubstituted parent compounds. Within the two series of novel phenyl ethers, we observed parallel shifts in affinity and, furthermore, the increase in α4β2/α3β4 selectivity resulting from the hydroxyalkynyl substitution parallels that reported for the same modification at the 3-pyridyl ether of ( S )- N -methylprolinol (A-84543), a well-known potent α4β2 agonist. On the basis of these results, our nitrophenyl and hydroxyphenyl prolinol ethers can be considered bioisosteres of the pyridyl ether A-84543 and lead compounds candidable to analogous optimization processes.